Youth's school experience: Testing the role of symptoms of anxiety and co‐occurring symptoms of depression. Issue 3 (12th November 2019) - Tan, Tony Xing; Teng, Yuejia; Velasco, Juliana C.
Abstract: Although symptoms of anxiety often coexist with symptoms of depression, little is known on how such coexistence affects youth's school experiences. Objectives: We tested how the two types of behaviors, when coexisting, were associated with youth's negative attitude toward teachers, school, and poor peer relations. Method: Data were collected from 203 ethnically and socioeconomically diverse youth (male: 24.6%; mean = 15.8 years, standard deviation = 2.4) with the 3rd edition of the Behavioral Assessment for Children: Self‐Report of Personality . Results: Scores for symptoms of depression alone explained negative attitude toward teachers ( β  = .28; R 2  = 17.88%), negative attitude toward school ( β  = .27; R 2  = 14.74%), and poor peer relations ( β  = .42; R 2  = 44.60%) as effectively as scores for both types of behaviors did. Conclusion: The coexistence of symptoms of anxiety and depression did not appear to impair youth's attitude toward teachers, school and peer relations more than symptoms of depression did alone.